2016
DOI: 10.1177/1362361316664868
|View full text |Cite
|
Sign up to set email alerts
|

Services for children with autism in the Kingdom of Saudi Arabia

Abstract: Little information is available about autism spectrum disorder services in the Kingdom of Saudi Arabia. A sample of 205 parents completed an online survey about the use of autism spectrum disorder services for their children. The results revealed that on average, children began services by 3.3 years. Most parents reported utilizing non-medical treatments followed by biomedical treatments and cultural and religious treatment. The age at the initiation of services and the type of treatments used differed by pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 22 publications
(63 reference statements)
6
65
2
Order By: Relevance
“…In the current study, caregivers were found to have waited on average more than one year to start contacting a health care professional and on average nearly 1.3 years to receive a formal ASD diagnosis, suggesting a delay of more than two years. This delay is similar to that experienced by caregivers in the UK [12] and more than one-half of that experienced by caregivers in Saudi Arabia [14]. The delay in seeking help reflects a lack of knowledge among certain caregivers about the importance of early diagnosis and intervention.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In the current study, caregivers were found to have waited on average more than one year to start contacting a health care professional and on average nearly 1.3 years to receive a formal ASD diagnosis, suggesting a delay of more than two years. This delay is similar to that experienced by caregivers in the UK [12] and more than one-half of that experienced by caregivers in Saudi Arabia [14]. The delay in seeking help reflects a lack of knowledge among certain caregivers about the importance of early diagnosis and intervention.…”
Section: Discussionsupporting
confidence: 67%
“…This finding is similar to those reported by Moh and Magiati [9] in Singapore. By comparison, in the UK, southeastern Europe and Saudi Arabia, caregivers first reported noticing developmental delays earlier, around their child’s second birthday [12,14,17]. The possible reason why Malaysian caregivers might recognize development delays later is that, in such collectivistic cultures, encroaching on other people’s business is discouraged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second perspective concerns the financial means of a household. Across different geographical contexts, the access to and quality of ASD services is associated with income (Alnemary, Aldhalaan, Simon-Cereijido, & Alnemary, 2017;Bishop-Fitzpatrick & Kind, 2017;Colbert, Webber, & Graham, 2017;Dickerson et al, 2017), with parents of lower socioeconomic status reporting poorer access (Bishop-Fitzpatrick & Kind, 2017) and poorer quality (S. Magaña, Parish, & Son, 2015) of care for their child with ASD. In addition to direct healthcare expenditures, indirect expenditures, such as transportation costs or opportunity costs of the caregiver missing out on incomegenerating activities, play a role (Daley, 2004;Minhas et al, 2015;Peters et al, 2008;Tilahun et al, 2016).…”
Section: Barriers In Help-seeking Behaviourmentioning
confidence: 99%
“…the quality of the road; availability of public transport services, etc) (Peters et al, 2008). Given the scarcity of mental health services and the often centralised location of services in or near larger cities (Saraceno et al, 2007), adequate access to diagnostic and intervention services is especially problematic for individuals living in more remote areas (Alnemary et al, 2017;Saxena et al, 2007). ASD studies from South Asian countries highlight how a limited number of specialists concentrated in big cities means it is prohibitively difficult for caregivers of children with ASD to seek help, with some families having to travel for days (Daley, 2004;Minhas et al, 2015).…”
Section: Barriers In Help-seeking Behaviourmentioning
confidence: 99%